MLTI-03. The relevance of the count of brain metastases for treatment and outcome in NSCLC. (9th August 2021) - Reinecke, David; Jünger, Stephanie T; Kocher, Martin; Ruge, Maximilian; Ruess, Daniel; Goldbrunner, Roland; Grau, Stefan J
Abstract: Background and Purpose: While data reporting the number of brain metastasis as a prognostic factor for patients with NSCLC, we analyzed whether the prognostic importance of the mere count of brain metastasis in a modern, multimodal treatment setting. Patients and Methods: We retrospectively analyzed patients treated for BM from non-small lung cancer between 2010 and 2020. Demographics, baseline characteristics, and tumor-associated parameters were retrieved from an electronic database. Prognostic factors for local cerebral control and survival were identified using the log-rank test and Cox regression analysis. Results: We included 343 consecutive patients (male n=187, female n=156; median age 61 years). Histological subtypes were adenocarcinoma (n=283), squamous-cell carcinoma (n=42) and neuroendocrine carcinoma (n=18). The median number of BM was one (range 1–20). Single (n = 189), oligo (n=110) and multiple BM (n=44) showed in total a median follow up of 10 months (minimum 1, maximum 142). Treatment comprised surgical resection (n=218) with radiotherapy, stereotactic radiosurgery (n=125) and adjuvant systemic therapy (n=203). The median local cerebral control was 11 months (95%CI 8.5 – 13.5) and the median overall survival was 16 months (95%CI 12.8 – 19.2). The number of BM did not influence local control and overall survival rates (p = 0.234 and p = 0.210, respectively). Controlled systemic disease (HR 0.42; 95% CI 0.2284–0.633; p<0.0001), clinical status (Karnofsky Performance Score > 70; HR 0.41; 95% CI 0.265–0.661; p<0.0001) and adjuvant systemic therapy (HR 0.38; 95% CI 0.279–0.530; p<0.0001) were independent prognostic factors for survival. Conclusions: The mere number of brain metastases is not a prognostic factor for survival and local cerebral control in a multimodal treatment setting.